AB0656 Nailfold videocapillaroscopy features of patients with antisynthetase syndrome. (15th June 2017) - Sebastiani, M; Codullo, V; Manfredi, A; Selva, A O'Callaghan; Furini, F; Iuliano, A; Schwarting, A; Cavagna, L; Triantafyllias, K; ,
Abstract : Background: Antisynthetase syndrome (ASSD) is an autoimmune disease characterized by the clinical triad arthritis, myositis, and interstitial lung disease (ILD). As in inflammatory myopathies, nailfold videocapillaroscopy (NVC) alterations have been sporadically described also in ASSD patients, but no elucidating data are available. Objectives: To investigate the possible specific NVC features of ASSD patients. Methods: Within the framework of a multicenter study, we retrospectively analyzed NVC images of ASSD patients, after excluding patients with overlap syndrome with systemic sclerosis. Two operators in a blind manner re-evaluated all patients with at least one image per finger. For each patient, we examined number of capillaries (mean number of capillaries per mm in the distal row), enlarged and giant capillaries, micro-hemorrhages, avascular areas, ramified capillaries, and the presence of a scleroderma (SSc)-like pattern, according to Manfredi et al. Finally, we correlated NVC features with clinical and serological findings of ASSD patients. Results: The NVC of 54 ASSD patients were analyzed (males/females 1/6.8, mean age 55.79, CI95% 51.9–59.9 years, mean disease duration 59.4, CI95% 27.9–90.9 months). Raynaud's phenomenon (RP) was recorded in 51.9% of patients, arthritis in 79.6%, myositis in 53.7%, and ILD in 92.6%. NVC alterations were observed in 53.7% of AASD patients. Nineteen patients (35.2%) showed a SSc-like pattern; the main features were disarrangement of hairpin and angiogenetic aspects (42.6%), avascular areas (38.9%), giant capillaries (27.6%), and microhemorrhages (20.4%). Finally, the mean number of capillaries was reduced (7.8±2/mm). No significant association was recorded between SSc-like pattern and the presence of arthritis, myositis, and ILD, nor with RP. Among other NVC features, angiogenesis was significantly associated to female gender (p=0.031), while microhemorrhages were inversely associated to the presence of arthritis (0.033). No association was observed between NVC features and autoantibodies profile. Of interest, in 58% of patients with ILD we observed at least a NVC alteration vs no patients without ILD (p=0.04). Finally, in patients with RP NVC alterations were recorded in 15/28 patients (53.6%) and a SSc-like pattern in 11/28 (39.3%), while only 57.9% of patients with SSc-like pattern had a clinically manifest Raynaud's phenomenon. Conclusions: Despite preliminary, the present is the first study concerning NVC in AASD patients. Regardless of the presence of Raynaud's phenomenon, NVC alterations are frequently observed; in particular, a SSc-like pattern is recorded in more than 1/3 of patients. NVC should be performed in all ASSD patients at diagnosis regardless of the presence of RP in the patient history and during follow-up. ASSD should be always considered in the screening of RP. A prospective multicenter study has been planned to identify specific patterns and possible associations between NVC findings and clinical and serological features of ASSD. References: Manfredi A, et al. 2015. Sebastiani M, et al. 2014. Disclosure of Interest: None declared